2019
DOI: 10.1093/milmed/usz071
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Emergency Medicine Resident Research Program in the United States Military

Abstract: Introduction The Accreditation Council for Graduate Medical Education stipulates that residents should participate in scholarly activity. As of 2019 that verbiage will be changed to, “Residents must participate in scholarship.” However, scholarly activity is not clearly defined. We set out to define our graduation research requirement in a measurable way and structure a research curriculum that better prepared residents to conduct scholarly activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Similarly, we saw no differences in the scholarly output in form of conference presentations at the state American College of Physician conference over the study period. Similar trends have been noted in other residency programs in the United States [14].…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, we saw no differences in the scholarly output in form of conference presentations at the state American College of Physician conference over the study period. Similar trends have been noted in other residency programs in the United States [14].…”
Section: Methodssupporting
confidence: 84%
“…In a recent study by Oliver, et al which evaluated the role of a dedicated research curriculum on resident scholarly output, residents who were exposed to a dedicated research curriculum had significantly higher number of scholarly activities as evidenced by PubMed indexed publications, online publications and conference presentations [14]. Beyond having a research curriculum, it appears mandating residents to submit scholarly work prior to graduation increased scholarly activity.…”
Section: Methodsmentioning
confidence: 99%
“…The 187 scholarly outputs generated by the CEP equate to 31.2 outputs per year, which is more than double the number of graduating residents per year. Prior studies have shown that, on average, residents generated 0.3–1.38 scholarly outputs each during a 3‐year residency 11,14,15,18 …”
Section: Discussionmentioning
confidence: 99%
“…Lack of a proper research schedule or curriculum was one of the most important and least considered issues on residency research activities, no matter in which country the program was. [12][13][14] Results of another study reported that the research curriculum was associated with long-term improvement of research products and more collaboration of residents and faculty. 15 Authorities believe that new strategies may be embedded in educational programs to increase residents' interest and their participation in research.…”
Section: Discussionmentioning
confidence: 99%